METODE RGEC MENJADI TOLAK UKUR TINGKAT KESEHATAN BANK - Moh. Abd. Rahman (Ar-Ribhu : Jurnal Manajemen dan Keuangan Syariah, 2022)
Background: Banks are the backbone of the economic and financial system in Indonesia as the channeling back of funds owned by excess economic units to economic units that need funds or deficits. The RGEC method is a structured way of assessing bank health compared to the previous valuation method, CAMELS. In article 2 paragraph (3) BI regulation No. 13/1 / PBI / 2011 concerning health assessment of commercial banks including risk profile, good corporate governance, earnings, and capital. Method: Document review is one of the research methods by comparing standards with financial statement documents to be examined. The documents that will be reviewed include the report on financial position, income statement and Good Corporate Governance report. The data that will be used in this study are quantitative data types. Quantitative data is numeric data such as financial position reports, income statements and other measurable data. Research Result: Seen from the four aspects measured in the form of risk profile, GCG, earnings, and capital as a whole are ranked very healthy even though there are differences in the value of the composite in each study year either overall BUKU IV Bank or individual banks, for the most consistent banks within the Bank BUKU IV category, according to the researchers, is BRI Bank because the composite value obtained by BRI each year is not too much different. Conclusion: The results of the analysis of the soundness of Bank BUKU IV namely BRI, BNI, Mandiri, BCA, and CIMB Niaga based on the RGEC method from 2012 to 2018 show that the bank's performance is in the Composite Rating 1 (PK-1) which means Bank BUKU IV is located in very healthy condition. Keywords: Bank Health, RGEC, BUKU